Statins interfere with the attachment of S. cerevisiae mtDNA to the inner mitochondrial membrane - Angela Cirigliano; Antonia Amelina; Beatrice Biferali; Alberto Macone; Chiara Mozzetta; Michele Maria Bianchi; Mattia Mori; Bruno Botta; Elah Pick; Rodolfo Negri; Teresa Rinaldi (Taylor & Francis Group, 2020)
The 3-hydroxy-3-methylglutaryl-CoA reductase, a key enzyme of the mevalonate pathway for the synthesis of cholesterol in mammals (ergosterol in fungi), is inhibited by statins, a class of cholesterol lowering drugs. Indeed, statins are in a wide medical use, yet statins treatment could induce side effects as hepatotoxicity and myopathy in patients. We used Saccharomyces cerevisiae as a model to investigate the effects of statins on mitochondria. We demonstrate that statins are active in S.cerevisiae by lowering the ergosterol content in cells and interfering with the attachment of mitochondrial DNA to the inner mitochondrial membrane. Experiments on murine myoblasts confirmed these results in mammals. We propose that the instability of mitochondrial DNA is an early indirect target of statins.